Примож Трубар: штрихи до портрета «словенського Лютера» - Шара, Л. (Сiверянський літопис, 2024)
Мета статті спрямована на з’ясування важливості зачинань протестантського проповідника Приможа Трубара для розвитку національної культури словенського народу, консолідації та етнічної ідентифікації в умовах іноземного поневолення. Методи дослідження: загальнонаукові – аналіз, синтез, конкретизація; та спеціально-історичні – історико-генетичний, біографічний, історико-системний, історико-порівняльний. Наукова новизна розвідки полягає в тому, що вона є спробою розкрити значимість літературної та друкарської ініціативи Приможа Трубара для націєтворчого процесу на словенських землях, підконтрольних Австрійській імперії. Опрацьовані матеріали дозволяють сформулювати такі висновки. Державотворення на словенських теренах розпочалося в ранньому середньовіччі з короткотривалої історії Карантанії та Блатенського князівства, які так і не змогли перетворитися на повноцінні ранньофеодальні монархії. Вони потрапили під зверхність Німецької, а згодом – Австрійської імперій, ставши «внутрішніми землями» габсбурзьких володінь. В умовах германізації та панування чужоземної еліти було надзвичайно важливим зберегти етнічні ознаки, з огляду на це, магістральною стала діяльність протестантського проповідника Приможа Трубара. Захопившись реформаційними ідеями й офіційно перейшовши у лютеранство, він спрямував свої знання і зусилля на формування словенської літературної мови та книгодрукування. Завдяки йому словенці отримали перші переклади біблійних текстів, богослужіння та початкову освіту рідною мовою, що, безперечно, позитивно позначилося на розвитку словенської культури, самоідентифікації народу, збереження його як самостійної спільноти, заклало фундамент для майбутнього національного Відродження й виходу словенців на політичну арену в ХІХ ст. The purpose of the publication is to clarify the importance of the initiatives by the Protestant preacher Primož Trubar for the development of the Slovenian’s national culture, consolidation and ethnic identification in the context of foreign enslavement. The research methods correlate with the stated goal. Therefore, general methods of science were used such as analysis, synthesis, specification, and historical methods, especially historical-genetic, biographical, historical-systemic and historical-comparative. The scientific novelty of the paper deals with an attempt to reveal the significance of Primož Trubarʼs literary and printing initiative for the nation-building process in Slovenian lands controlled by the Austrian empire. The materials analyzed allow us to formulate the following conclusions. State-building on Slovenian territories began in the early Middle Ages with the short-lived history of Carinthia and the Principality of Blaten which failed to develop into full-fledged early feudal monarchies. They came under the domination of the German and later Austrian empires, becoming the «inner lands» of the Habsburg domains. In the context of Germanization and the domination of a foreign elite, it was extremely important to preserve ethnic characteristics, so the activities of the Protestant preacher Primož Trubar became a major factor in this direction. Fascinated by the Reformation ideas and officially converting to Lutheranism, he directed his knowledge and efforts to the formation of the Slovenian literary language and book printing. Thanks to him, the Slovenes received the first translations of biblical texts, worship services and primary education in their native language, which undoubtedly had a positive impact on the development of Slovenian culture, selfidentification of the people, preservation of the nation as an independent community, and laid the foundation for the future national Renaissance and the Slovenesʼ entry into the political arena in the nineteenth century.